2020
DOI: 10.1002/adhm.201901805
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy for Treating Inflammatory Bowel Disease by Targeting Delivery of Methotrexate through Glucan Particles

Abstract: Therapy of inflammatory bowel disease (IBD) has been a difficult task in the medical field. There is a great clinical need for more effective treatments for IBD. Herein, a targeted oral delivery system of yeast glucan particles (YGPs) carrying a clinically used anti‐inflammatory drug methotrexate (MTX) to the inflamed sites in IBD mice for therapy is reported. In the findings, MTX is effectively loaded into YGPs through re‐precipitation followed by gelation reaction of alginate to obtain the composite YGPs/MTX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…This work aims to combine aPDT and silver into hybrid nanocarrier to combat bacteria. In addition, the methotrexate (MTX) is also included in the nano-carrier to treat the inflammatory reaction associated with bacterial infection (Lebugle et al, 2002;Alam et al, 2017;Yang et al, 2017;Duan and Li, 2018;Trujillo-Nolasco et al, 2019;Sun et al, 2020). To address the aforementioned issues of bare silver nanoparticles, different nano-carriers have been constructed, such as metalorganic frameworks (MOFs) (Ximing et al, 2017;Zhang et al, 2019Zhang et al, , 2020, hybrid metallic nanoparticles (Mahmoudi and Serpooshan, 2012;Durmus and Webster, 2013;Mei et al, 2013;Shah et al, 2013;Agnihotri et al, 2015;Lim et al, 2015;Kyaw et al, 2017;Kim et al, 2018;Liu et al, 2018;Gasmalla et al, 2019;He et al, 2020;Tong et al, 2020) and mesoporous nanoparticles (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This work aims to combine aPDT and silver into hybrid nanocarrier to combat bacteria. In addition, the methotrexate (MTX) is also included in the nano-carrier to treat the inflammatory reaction associated with bacterial infection (Lebugle et al, 2002;Alam et al, 2017;Yang et al, 2017;Duan and Li, 2018;Trujillo-Nolasco et al, 2019;Sun et al, 2020). To address the aforementioned issues of bare silver nanoparticles, different nano-carriers have been constructed, such as metalorganic frameworks (MOFs) (Ximing et al, 2017;Zhang et al, 2019Zhang et al, , 2020, hybrid metallic nanoparticles (Mahmoudi and Serpooshan, 2012;Durmus and Webster, 2013;Mei et al, 2013;Shah et al, 2013;Agnihotri et al, 2015;Lim et al, 2015;Kyaw et al, 2017;Kim et al, 2018;Liu et al, 2018;Gasmalla et al, 2019;He et al, 2020;Tong et al, 2020) and mesoporous nanoparticles (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“… 84 Sun et al synthesized yeast cell wall-coated immunosuppressive agent methotrexate (MTX)-loaded nanoparticles (YGPs/MTX) for targeted IBD therapy. 85 Taken orally, the drug-loaded system preferentially internalized into macrophages, which promoted the uptake of MTX by macrophages, leading to the suppression of NO, TNF-α, IL-6, and IL-1β secretion. With the active targeting effects, the YGPs/MTX showed excellent anti-inflammatory effects in vivo.…”
Section: Passively and Actively Targeted Drug Deliverymentioning
confidence: 99%
“…Accordingly, yeasts have been adopted to deliver many pharmaceutical agents, including small-and large-molecule drugs (45)(46)(47), genetic materials (48), and vaccines (49). For example, an oral delivery of yeast glucan particles carrying methotrexate, an anti-inflammatory drug, was shown to be effective in treating mice with inflammatory bowel disease (50). The study reported that drug-containing yeast glucan particles were internalized through macrophages, with subsequent down-regulation of macrophage-induced pro-inflammatory cytokines.…”
Section: Yeasts As Oral Vaccine and Gene Delivery Agents Yeast Characteristicsmentioning
confidence: 99%